In vitro Antibiofilm Activity of Pomegranate (Punica granatum) Juice on Oral Pathogens - Jemima Pramadita; Armelia Sari Widyarman (Journal of Indonesian Dental Association, 2019)
Introduction: Pomegranate (Punica granatum) fruit contains valuable ingredients, such as ellagitannins and flavonoids, that have many potential effects, including antibacterial, antifungal, and anti-inflammatory functions. Objectives: The aim of this study was to investigate the effects of pomegranate fruit juice on F. nucleatum and S. sanguinis monospecies and multispecies biofilm formation in vitro. Methods: Pomegranate juice was obtained using a juicer and diluted using a brain heart infusion (BHI) broth into five different concentrations. The biofilm assay was performed as follows: F. nucleatum and S. sanguinis were cultured separately in the BHI broth for 48 hours at 37°C in an anaerobic atmosphere. A 200 mL bacterial suspension (107 CFU/mL) was distributed into a 96-well plate and incubated for 24 hours to form a biofilm. Subsequently, pomegranate juice was added to the biofilm well and observed after 1 hours, 3 hours, 6 hours, and 24 hours. The biofilm mass was measured using a microplate reader (490 nm) after crystal violet staining. Chlorhexidine (0.2%) and the biofilms without treatment were used as the positive and negative controls, respectively. The data were statistically analyzed using one-way analysis of variance, with p<0.05 as the level of significance. Result: There was a significant biofilm reduction after treatment with pomegranate juice for all the concentrations and incubation times (p<0.05). The effective concentrations to inhibit the biofilm monospecies F. nucleatum and S. sanguinis and the multispecies were 6.25% (OD 0.148±0.019), 50% (OD 0.211±0.026), and 6.25% (OD 0.024±0.209), respectively. Conclusion: Pomegranate juice inhibits F. nucleatum and S. sanguinis biofilm formation as a monospecies and a multispecies. Future studies are needed to observe the mechanism of this active substance.